ANALISIS DAMPAK PANDEMI COVID-19 TERHADAP PERUBAHAN STRUKTUR PEREKONOMIAN PROVINSI LAMPUNG - Pratikno, Dimas Dwi (Universitas Islam Negeri Raden Intan Lampung, 2021)
The Covid-19 pandemic that has hit the entire world has caused a decline in economic activity, including in Indonesia and Lampung Province to a lesser extent. Therefore, it is necessary to analyze the latest economic conditions, especially in the identification of the affected sectors and sub-sectors. Regional economic growth is seen through GDP so that it becomes the data needed in this study in the 2015-2020 data period in Lampung Province. The research method used analysis techniques Location Quotient (LQ), Shift-Share, and Typology Klassen to identify sectors and sub-sectors affected by the Covid-19 pandemic in Lampung Province. The results show that several sub-sectors experienced a decline, such as the sub-sector of Machinery and Equipment Industry, Motor Vehicle Trade and Repair, Rail Transport, and Air Transport, which before the pandemic were the base sub-sector to the non-base sub-sector. Shift-share analysis shows the results of an increase in all sectors with the manufacturing sector experiencing greater growth. Klassen's typology analysis shows the results in the form of a shift in the transportation and warehousing sectors into prime sectors and into quadrant1 before entering into quadrant 3, and the information and communication sector experiencing a sector shift to a lagging sector and into quadrant 4.